DEVELOPMENT OF THERAPEUTIC VACCINE FOR GERIATRIC MEDICINE. (16th November 2018) - Nakagami, H; Yoshida, S; Nakajima, T; Takeda, S; Rakugi, H
Abstract: Recent research on vaccination has extended its scope from infectious diseases to chronic diseases, and we have reported that angiotensin II vaccine for hypertension or DPP4 vaccine for diabetes successfully attenuated the high blood pressure with its complications or hyperglycemia in each mice model, respectively (PLoS One 2013, PNAS 2014, Stroke 2017, Sci Rep 2017). Here, we proposed a novel concept of our therapeutic vaccine for aging-related diseases. First target of our approach is S100A9 (S100 calcium-binding protein A9), one of alarmins released from platelet or macrophage as a trigger of inflammation. S100A9 vaccine successfully induced anti-S100A9 antibody without cytotoxic reaction. Since S100A9/CD36 signaling contributes thrombus formation, the immunized mice were exposed to vascular injury for thrombosis formation. The occlusion time was significantly delayed in the mice immunized with S100A9 vaccine, which was comparable to that in the mice treated with 6 mg/kg clopidogrel. In the evaluation of coagulation system, there was no significant difference in tail bleeding time between S100A9-vaccinated mice and the control mice, whereas tail bleeding time in the mice treated with clopidogrel was significantly longer. Second approach of our strategy is to deplete the aging-cells by therapeutic vaccine which mimic senolysis therapy. We successfully developed the vaccine for aging T-cells. Under high fat diet, administration of the vaccine decreased the numbers of aging T-cells in white adipose tissue and the immunized mice improved systemic glucose intolerance in mice. These novel immunotherapies may contribute the preventive medicine to control the chronic inflammation with aging.